2022
DOI: 10.3390/biomedicines10061225
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Antipsychotic-Induced NAFLD and Iron Dysregulation: A Multi-Omic Approach

Abstract: Atypical antipsychotic (AA) medications are widely prescribed for the treatment of psychiatric disorders, including schizophrenia, bipolar disorder and treatment-resistant depression. AA are associated with myriad metabolic and endocrine side effects, including systemic inflammation, weight gain, dyslipidemia and insulin resistance, all of which are associated with increased incidence of non-alcoholic fatty liver disease (NAFLD). NAFLD is highly prevalent in patients with mental illness, and AA have been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
3
0
4
Order By: Relevance
“… 36 , 37 The side effects associated with antipsychotic medications, such as dyslipidemia, weight gain, systemic inflammation, and insulin resistance, increase the incidence of NAFLD. 38 , 39 Centorrino et al 40 found that when the total dose of antipsychotics was similar, there was a 56% higher risk of adverse effects and a 55% longer hospital stay in patients with SCZ treated with APP compared to SCZ patients treated with monotherapy. A review by Gallego et al found that APP is strongly associated with metabolic abnormalities such as hyperprolactinemia and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 The side effects associated with antipsychotic medications, such as dyslipidemia, weight gain, systemic inflammation, and insulin resistance, increase the incidence of NAFLD. 38 , 39 Centorrino et al 40 found that when the total dose of antipsychotics was similar, there was a 56% higher risk of adverse effects and a 55% longer hospital stay in patients with SCZ treated with APP compared to SCZ patients treated with monotherapy. A review by Gallego et al found that APP is strongly associated with metabolic abnormalities such as hyperprolactinemia and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Omics technologies, including genomics, epigenomics, transcriptomics, proteomics, metabolomics, lipidomics and 10.3389/fnins.2022.1042442 glycomics, are high throughput analytical tools that enable bioanalysis of complex pathophysiological and pharmacological dynamics (Perakakis et al, 2020). Recent studies utilizing proteomic approaches have identified myriad signaling pathways that are disrupted by clinically relevant AA exposures in pre-clinical and clinical samples that are associated with significant changes in multiple NAFLD associated pathways including those regulating lipid metabolism, mitochondrial function, inflammation, iron metabolism and insulin signaling (May et al, 2019(May et al, , 2020(May et al, , 2022Beauchemin et al, 2020;Rostama et al, 2020).…”
Section: Mechanistic Toxicology Of Atypical Antipsychotic Medications...mentioning
confidence: 99%
“…Serum measures in psychiatric patients can be complicated by multiple treatment confounders; however, case-controlled studies with drug-naïve patients still support a direct association between psychosis and serum iron concentrations ( Cao et al, 2019 ; Owiredu et al, 2019 ). Additionally, antipsychotic medications themselves can alter iron metabolism ( May et al, 2022 ). Patients with metabolic liver disease have been reported to have altered levels of serum ferritin, hemoglobin, and hematocrit ( Li et al, 2012 , 2014 ; Bernhardt et al, 2018 ; Jung et al, 2019 ), and hemoglobin has been reported as an independent predictor of fibrosis in lean patients with NAFLD ( Akyuz et al, 2015 ) and NASH ( Nelson et al, 2007 ).…”
Section: Mechanistic Synergies Between Non-alcoholic Fatty Liver Dise...mentioning
confidence: 99%
“…Гематологические проявления НАЖБП включают синдром дисметаболической перегрузки железом (СДПЖ). СДПЖ характеризуется стеатозом, умеренным отложением железа в тканях, и повышенным уровнем ферритина в сыворотке крови при нормальном насыщении трансферрина сыворотки железом [3,4].…”
Section: Introductionunclassified
“…Нарушения обмена железа встречаются, в среднем, у 1/3 пациентов с НАЖБП [4]. В частности, эпидемиологическое исследование населения северо-восточной Германии (n = 2561) показало, что распространенность НАЖБП составила 42% (легкая форма -28,5%, умеренная -12%, тяжелая -1,8%).…”
Section: Introductionunclassified